Case Report: Drug Related Supraventricular Tachycardia in A 58-Year-Old Male with Lung Tuberculosis - Wira Putri, Atina Irani; Hidayah, Rizka Nurul (Direktorat Riset dan Pengabdian Kepada Masyarakat, Institut Teknologi Sepuluh Nopember, 2025)
Background: Arrhythmia in tuberculosis is a rare and life-threatening condition. It can occur as an adverse effect of drugs included in the regiment. Case presentation: This study reported a case of arrhythmia in a 58-year-old male who experienced sudden onset of palpitations, several days after his tuberculosis regiment was changed from the fixed drug combination to a non-hepatotoxic regiment. Based on the clinical presentation, electrocardiogram, laboratory finding, echocardiogram, and analysis of the adverse effects of all given drugs, a drug was suspected as the cause of his arrhythmia. The patient survived after undergoing acute phase management for arrhythmia and discontinuation of the culprit drug. Discussion: One of the serious adverse effects of fluoroquinolone is prolonged QT intervals that could lead to deadly arrhythmia. Therefore, close monitoring of the clinical, vital, and physical is crucial, especially during the first month of therapy. Conclusion: Conscientious consideration should be made before starting therapy for tuberculosis, and acute phase management is pivotal in termination of arrhythmia.